2019
DOI: 10.1007/s12350-017-0905-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CT-based attenuation correction on the automatic perfusion score of myocardial perfusion imaging using a dedicated cardiac solid-state CZT SPECT/CT

Abstract: Specifically designed databases for solid-state CZT cardiac SPECT provide accurate quantitation of perfusion scores concordant with those previously validated for conventional SPECT. AC and NAC CZT scores differed significantly, especially in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…These studies demonstrated improved diagnostic confidence and accuracy with CT AC. [5][6][7] Recently, Kennedy et al demonstrated that specifically designed databases for solid-state CZT cardiac SPECT provide accurate quantitation of perfusion scores concordant with those previously validated for conventional SPECT 8 (Figures 1 and 2). It is important to point out that the same concordance was not achieved using solely the normal default database available for the conventional system.…”
supporting
confidence: 52%
“…These studies demonstrated improved diagnostic confidence and accuracy with CT AC. [5][6][7] Recently, Kennedy et al demonstrated that specifically designed databases for solid-state CZT cardiac SPECT provide accurate quantitation of perfusion scores concordant with those previously validated for conventional SPECT 8 (Figures 1 and 2). It is important to point out that the same concordance was not achieved using solely the normal default database available for the conventional system.…”
supporting
confidence: 52%
“…2 Many of these studies have assessed the diagnostic performance of MPI with CZT cameras (Table 1). 1,[3][4][5][6][7][8] Further, in a meta-analysis by Nudi et al, the sensitivity of CZT SPECT was found to be range between 0.78 and 0.89 and the specificity ranged from 0.62 to 0.76. 9 While the sensitivity is comparable to prior studies, the specificity is lower.…”
Section: Czt Versus Conventional Spectmentioning
confidence: 95%
“…Kennedy et al 1 demonstrate a reasonable correlation between CZT and conventional NaI scanners. Their data are in agreement with prior studies that indicate CZT could be associated with lower specificity and a higher number of false positives.…”
Section: Czt Versus Conventional Spectmentioning
confidence: 95%
See 2 more Smart Citations